Typhoons : climate, society and history of the Philippines - Warren, James Francis (Quezon City, Philippines : Ateneo De Manila University Press, 2024)
This book offers an unprecedented and extensive view of the complex interplay of typhoons and Philippine society.
Part 1. The Riddle -- Part 2. The Rampage -- Part 3. The Response -- Part 4. The Reckoning.
Includes bibliographical references and index.
Keywords: TYPHOONS -- HISTORY -- PHILIPPINES -- SOCIAL ASPECTS